2014
DOI: 10.3329/jbsa.v22i1.18095
|View full text |Cite
|
Sign up to set email alerts
|

Audit of general intensive care unit of Bangabandhu Sheikh Mujib Medical University

Abstract: All patients admitted to the Intensive Care Unit of BSMMU between January 2006 and December 2006 on whom data had been entered into the study. A total of 473 admissions with complete records were available. Hospital mortality was 60.6%. Nonsurvivors were older than survivors and had longer ICU stays. Patients admitted from wards had a higher mortality than patients from the operating room/ recovery or the emergency department. Thirty-four percent of patients were in the ICU for >2 days, and they accounted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…length of stay and organizational aspects of the unit and corresponding mortality in the hospitalized patients was 30 to 42.2% 10,11,12 . A study done in CMH Dhaka, it was found that the incidence of mortality was more in medical discipline (46.14%) than surgical discipline (31%) and least in gynaecological and other disciplines (15.62%) and total ICU mortality rate was 39.69% 13 .Another study done in ICU Bangabandhu Sheikh Mujib Medical University, Dhaka from January 2006 to December 2006 Overall mortality of ICU admitted patient were 60.61% 14 . In our study, it was found that the incidence of mortality was more in gynaecological and other disciplines (61.53%) than medical discipline (55.76%%) and least in surgical discipline (43.35%) and total ICU mortality rate was 51%, which is comparable to other ICUs ( Table -II…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…length of stay and organizational aspects of the unit and corresponding mortality in the hospitalized patients was 30 to 42.2% 10,11,12 . A study done in CMH Dhaka, it was found that the incidence of mortality was more in medical discipline (46.14%) than surgical discipline (31%) and least in gynaecological and other disciplines (15.62%) and total ICU mortality rate was 39.69% 13 .Another study done in ICU Bangabandhu Sheikh Mujib Medical University, Dhaka from January 2006 to December 2006 Overall mortality of ICU admitted patient were 60.61% 14 . In our study, it was found that the incidence of mortality was more in gynaecological and other disciplines (61.53%) than medical discipline (55.76%%) and least in surgical discipline (43.35%) and total ICU mortality rate was 51%, which is comparable to other ICUs ( Table -II…”
Section: Discussionmentioning
confidence: 97%
“…In our country, by the time the patients reach into the ICU, it was identified that the patient remain in high risk or death, because of severe compromised physiological reserve and irreversible organ failure and it may be too late to do much influence the outcome of those who die within 12 hours to 48 hours of admission. Such patients are head injury, severe hypoxia, end stage organ failure and terminal cancer 14 . In this study it was found that the incidence of medical disease related mortality rate within 24 hours was 35 (42%) out of 82 patients, head injury and surgical patient was 23(41.01%) out of 55 (Table-V).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately our postoperative care is based on isolation of patients only and minimal facilities are available. Therefore, surgical team and patients´ party prefer to shift these patients to the intensive care unit [6]. Because judicious use of drugs, bloods and fluids, restoration of cardiac output and blood pressure, control of temperature, provision of appropriate nutrition, analgesia and respiratory support are only available in the intensive care unit.…”
Section: Introductionmentioning
confidence: 99%